Changing Money Viewed From Positive Law and Islamic Law - Arifin S.H., M.Hum, Dr. Muhammad (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
Money can be interpreted through several views and generally money can be encountered through two views, the first definition of money in terms opf legal views and the sense of money in terms of the view function.